Implementing Tolerance Values and Patriotsm Through History Learning at SMA Negeri 11 Yogyakarta - Muslim Muslim; Warto Warto; Djono Djono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to obtain: (1) inculcating the values of tolerance and patriotism through learning history, (2) difficulties experienced by history teachers, and (3) efforts made by history teachers to overcome these difficulties. This study uses qualitative methods, with a single embedded case study strategy. This study was conducted at SMA Negeri 11 Yogyakarta. Data were collected through observation, in-depth interviews, and document study. The data analysis technique used the interactive model of Miles and Huberman's analysis. The results of the study show that: (1) Cultivating the values of tolerance and patriotism, namely through learning preparation, learning implementation, (using the discussion method, because in discussions it is easy to instill the values of tolerance and patriotism in students), and evaluation. (2) The difficulty faced by history teachers is that they have little time to study, and nowadays online learning makes it difficult for teachers to socialize with students. (3) Efforts made by history teachers, in overcoming these difficulties, were to make themselves role models and motivators for their students. In the end, after the obstacles are overcome, the values of tolerance and patriotism increase.